LEVELS OF CLASS AWARENESS AND WEALTH REPRESENTATIONS AMONG A SAMPLE OF ALGERIAN UNIVERSITY YOUTH - Radhouane Moumene; Fatima Drouche; Djamila Charif (International Journal of Innovative Technologies in Social Science, 2025)
The study of consciousness has represented a central issue in sociological research aimed at understanding societies, as consciousness forms the foundation of group affiliation, the adoption of its roles and functions, and even the shared representations of various societal issues. Researchers have consistently emphasized the significant role of value-based and social representations in shaping collective imaginaries and crafting perspectives on different issues among members of a single group. Based on this premise, the present study examines the levels of awareness of class affiliation in Algerian society and representations of wealth among a sample of university youth. It provides a detailed description of the degrees of awareness concerning class stratification and affiliation, along with an overview of some representations of wealth as a crucial societal issue affecting this demographic. The study also reveals certain contradictions related to the values shaping social representations of wealth among this group, opening avenues for further research in this field.